Integrating Web Technologies with Augmented Reality - Rafdhi, Agis Abhi (Universitas Komputer Indonesia, 2024)
This study aims to provide a comprehensive review of the integration between web technologies and augmented reality (AR) in engineering and computing contexts. Using a structured literature review method, 75 peer-reviewed articles published between 2019 and 2024 were selected based on defined criteria, including relevance, scope, and methodological quality. The findings reveal that WebAR enhances accessibility, interactivity, and real-time visualization, particularly in education, remote maintenance, and smart systems. Despite these advantages, several challenges persist, such as limited infrastructure, technical constraints, and lack of curriculum alignment. This research concludes that a cross-disciplinary approach is essential to fully realize the potential of AR through scalable web-based frameworks, supported by collaboration among educators, developers, and system engineers.